Student satisfaction in student affairs management: the role of cross-functional cooperation in Hainan, China - Erlin Tian; Supot Rattanapun (Institute of Advanced Engineering and Science, 2026)
Student affairs management (SAM) is increasingly expected to deliver timely, coherent, and student-centered services, yet satisfaction remains uneven in Chinese universities because students experience SAM as an integrated system rather than isolated units. This study asks whether cross-functional cooperation (CFC) explains how service quality, service gaps, and students’ psychological and engagement factors translate into satisfaction with SAM in Hainan Province, China. Using a cross-sectional survey of 250 undergraduate and postgraduate students from ten public and private universities, the study applies partial least squares–structural equation modeling (PLS-SEM) with 5,000-sample bootstrapping to test direct and mediating effects. Results show that CFC is the strongest predictor of satisfaction (β=0.419, p<0.001). Service gaps reduce satisfaction (β=−0.217, p<0.001), while psychological and engagement factors increase satisfaction (β=0.206, p<0.001). Service quality has no direct effect but operates through CFC, indicating that coordination is required to convert service inputs into positive experiences. The findings highlight governance reforms that institutionalize cross-department coordination, shared case management, and gap monitoring to improve SAM effectiveness under Hainan’s reform context.